"The Last Refuge of the Incompetent": Urban Teacher Perceptions of Their Positions in Public Discourse. Issue 1 (2nd January 2021) - Aronson, Brittany; Anderson, Ashlee B.; Ellison, Scott; Barczak, Kristan; Bennett-Kinne, Andrea
Abstract: We present one subset of findings from a larger study of twenty-one practicing urban teachers regarding their perceptions of their positioning in public discourses. We begin with a general introduction, focusing primarily on the myth of the "bad teacher, " after which we provide an overview regarding the evolution of this myth, as well as the overall deprofessionalization of teachers that accompany it. Next, we present our methodology, which we label a focus group interview study. We then present our findings, focusing on the nuances targeted by the participants with whom we spoke. We conclude with an overall discussion of the harm done by this particular positioning, calling on policymakers to make more active use of teacher perspectives regarding their practice.